Clinical and translational advances in glioma immunotherapy: review - Bunse, Lukas; Bunse, Theresa; Krämer, Christopher; Chih, Yu-Chan; Platten, Michael (Neurotherapeutics, 2022)
Gliomas are highly treatment refractory against immune checkpoint blockade, an immunotherapeutic modality that revolutionized therapy for many tumors. At the same time, technological innovation has dramatically accelerated the development of immunotherapeutic approaches such as personalized tumor-specific vaccine production, dendritic cell vaccine manufacture, patient-individual target selection and chimeric antigen receptor, and T cell receptor T cell manufacture. Here we review recent clinical and translational advances in glioma immunotherapy with a focus on targets and their cognate immune receptor derivates as well as concepts to improve intratumoral T cell effector functions.
Online verfügbar: 27. Oktober 2022, Artikelversion: 1. Januar 2024
Gesehen am 29.01.2024